Validity and Reliability of the Finnish Diabetes Risk Core Questionnaire Indonesia with the Rasch Model Approach - Heri Budiawan; Idhfi Marpatmawati; Yuyun Solihatin; Bayu Brahmantia (INDOGENIUS, 2026)
Background and Objective: Type 2 diabetes mellitus is an increasing public health concern in Indonesia, with many individuals remaining undiagnosed due to limited early detection strategies. The Finnish Diabetes Risk Score is a non-invasive screening tool widely used to estimate the risk of developing type 2 diabetes, yet its Indonesian version has not been comprehensively evaluated using advanced measurement methods. This study aimed to assess the validity and reliability of the Indonesian version of the Finnish Diabetes Risk Score using the Rasch Model to ensure its appropriateness for community-based screening. Method: A quantitative, non-experimental study with a cross-sectional design was conducted among adults aged over 20 years who visited a primary health care center in Tasikmalaya. Participants were selected using accidental sampling. Data were collected through the Indonesian version of the Finnish Diabetes Risk Score questionnaire and analyzed using the Rasch Model to evaluate item fit, reliability, separation indices, and item difficulty hierarchy. Result : The findings showed high item reliability and strong item separation, indicating a stable and consistent hierarchy of diabetes risk factors. All items demonstrated acceptable fit to the Rasch Model, supporting the construct validity of the instrument. Conclusion: Although person reliability was relatively low, suggesting limited variability in respondent risk levels. Conclusion: Overall results confirm that the Indonesian version of the Finnish Diabetes Risk Score is valid and reliable at the item level and suitable for identifying individuals at risk of type 2 diabetes mellitus in community settings.